Small electron transfer proteins as mediators in enzymatic electrochemical biosensors - Silveira, Célia M. (2013)
"Electrochemical mediators transfer redox equivalents between the active sites of enzymes and electrodes and, in this way, trigger bioelectrocatalytic redox processes. This has been very useful in the development of the so-called second generation biosensors, where they are able to transduce the catalytic event into an electrical signal. Among other pre-requisites, redox mediators must be readily oxidized/reduced at the electrode surface and easily interact with the biorecognition component. Small chemical compounds (e.g. ferrocene derivatives, ruthenium or osmium complexes and viologens) are frequently used for this purpose, but lately, small redox proteins (e.g. horse heart cytochrome c) have also played the role of redox partners in biosensing applications. In general, the docking between two complementary proteins introduces a second level of selectivity to the biosensor and enlarges the list of compounds targeted for analysis. Moreover, electrochemical interferences are frequently minimized owing to the small overpotentials achieved. This paper aims to provide an overview of enzyme biosensors that are mediated by electron transfer proteins. The article begins with a few considerations on mediated electrochemistry in biosensing 2 systems and proceeds with a detailed description of relevant works concerning the cooperative use of redox enzymes and biological electron donors/acceptors."